Causal effects for genetic variants of osteoprotegerin on the risk of acute myocardial infarction and coronary heart disease: A two-sample Mendelian randomization study - Chao, Peng; Zhang, Xueqin; Zhang, Lei; Cui, Xinyue; Wang, Shanshan; Yang, Yining (Frontiers in Cardiovascular Medicine, 2023)
Although since the 1980s, the mortality of coronary heart disease(CHD) has obviously decreased due to the rise of coronary intervention, the mortality and disability of CHD were still high in some countries. Etiological studies of acute myocardial infarction(AMI) and CHD were extremely important. In this study, we used two-sample Mendelian randomization(TSMR) method to collect GWAS statistics of osteoprotegerin (OPG), AMI and CHD to reveal the causal relationship between OPG and these two diseases. In total, we identified 7 genetic variants associated with AMI and 7 genetic variants associated with CHD that were not found to be in linkage disequilibrium(LD; r2 < 0.001). Evidence of a positive effect of an OPG genetic susceptibility on AMI was discovered(IVW OR = 0.877; 95% CI = 0.787–0.977; p = 0.017; 7 SNPs) and CHD (IVW OR = 0.892; 95% CI = 0.803–0.991; p = 0.033; 7 SNPs). After removing the influence of rs1385492, we found that there was a correlation between OPG and AMI/CHD (AMI: weighted median OR = 0.818;95% CI = 0.724–0.950; p = 0.001; 6SNPs;CHD: weighted median OR = 0.842; 95% CI = 0.755–0.938; p = 1.893 × 10−3; 6SNPs). The findings of our study indicated that OPG had a tight genetic causation association with MI or CHD. This genetic causal relationship presented us with fresh ideas for the etiology of AMI and CHD, which is an area of research that will continue in the future.